Pengaruh Tegangan Tabung (Kv) pada Pemeriksaan Thorax terhadap Kualitas Citra Radiografi di RS Efarina Pangkalan Kerinci - Kustoyo, Bambang; Saragih, Christine Dear Hara (3031-8572, 2022)
X-ray tube voltage is one of the exposure factors that significantly influence the quality of radiographic images. The use of standard versus high voltage can impact the contrast and sharpness of thoracic radiographic images. This study aims to determine the effect of variations in tube voltage in thoracic examinations on radiographic image quality. This experimental study was conducted at Efarina Hospital, Pangkalan Kerinci, using a Toshiba X-ray machine model DRX-1824B. Irradiation was carried out using standard voltage (50-70 kV) and high voltage (90-110 kV) with a distance of 100 cm and a time of 10 mAs. Image quality was analyzed using Image-J software with a histogram feature. Standard voltage (50 kV) produced good radiographic image quality with clear histogram readings, showing the black background position from 16 to 36 and the object position from 37 to 79, allowing clear differentiation between the object edge and the background. High voltage (90 kV) results in reduced contrast, with a dominant grayscale gradient from positions 10 to 132, making objects and background indistinguishable. Standard tube voltage provides better radiographic image quality than high voltage for thoraxt examinations.